Midwife skill training as a family assistance team in preventing stunting in Tegal City - Fitriani Nur Damayanti; Rahayu Astuti; Siti Istiana; Avisa Zahra Paramitha (Universitas Muhammadiyah Magelang, 2023)
Stunting is still a health problem that requires attention because it affects physical growth and interferes with children's intelligence. Midwives are one of the personnel who provide oversight to ensure that nutrition and reproductive health education programs continue in the first 2 years of a baby's life, as well as monitoring the growth and development of the baby, which can help prevent stunting. The purpose of this community service is to increase the knowledge and skills of the family assistance team in collecting data and identifying the risk of stunting in Tegal city. The results of the activity show that training on data collection and identification of stunting risks using lecture and practice methods can increase midwives' knowledge in preventing stunting in Tegal City.